A fuzzy decision system for genetically modified plant environmental risk assessment using Mamdani inference. Issue 3 (15th February 2015) - Camastra, Francesco; Ciaramella, Angelo; Giovannelli, Valeria; Lener, Matteo; Rastelli, Valentina; Staiano, Antonino; Staiano, Giovanni; Starace, Alfredo
Highlights: A fuzzy system for environmental risk assessment of genetically modified plants is described. The fuzzy system is based on Mamdani inference. The Fuzzy System Risk Assessments have been validated on real world trial case studies. The system decisions have been considered coherent and consistent by human experts. Abstract: Environmental risk assessment (ERA) of the deliberate release of genetically modified plants (GMPs) is currently performed by human experts on the basis of own personal experience and knowledge. In this paper we describe a fuzzy decision system (FDS) for the ERA of GMPs, based on Mamdani fuzzy inference. The risk assessment in the FDS is obtained by using a fuzzy inference system (FIS), performed using jFuzzyLogic library. The FDS permits obtaining an evaluation process for the identification of potential impacts that can achieve one or more receptors through a set of migration paths. The decisions derived by FDS have been validated on real world cases by the human experts that are in charge of ERA. They have confirmed the reliability and correctness of the fuzzy system decisions.